EFEKTIVITAS PEMBERIAN TABLET TAMBAH DARAH TERHADAP KADAR HEMOGLOBIN PADA SISWI - Susanti, Reni; Krihariyani, Dwi; Endarini, Lully Hanni; Suliati, Suliati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Iron deficiency anemia is a common nutritional problem among adolescent girls in developing countries such as Indonesia, affecting both health and academic performance. The government has implemented a school-based iron supplementation program to address this issue. This study aims to evaluate the effectiveness of iron tablet supplementation in increasing hemoglobin levels among 10th-grade female students at MAN 3 Magetan. The study used a quasi-experimental design with a one-group pre-test and post-test approach. A total of 122 students aged 15–18 years participated based on inclusion criteria and parental consent. The intervention involved weekly iron tablet supplementation for three months. Hemoglobin levels were measured before and after the intervention using a HemoCue device, and data were analyzed using the Wilcoxon Signed-Rank test. The results showed a significant increase in hemoglobin levels after the intervention (p < 0.05). Prior to supplementation, 39% of the students were anemic, which decreased to 8% after the intervention, with 92% having normal hemoglobin levels. These findings indicate that regular iron supplementation effectively improves hemoglobin levels and reduces anemia prevalence. The program should be continued with sustained nutrition education and monitoring of compliance to ensure long-term effectiveness. ABSTRAK Anemia defisiensi zat besi merupakan masalah gizi yang umum pada remaja putri di negara berkembang seperti Indonesia, berdampak pada kesehatan dan prestasi belajar. Pemerintah telah menjalankan program pemberian tablet tambah darah (TTD) di sekolah sebagai upaya pencegahan. Penelitian ini bertujuan mengevaluasi efektivitas pemberian TTD terhadap peningkatan kadar hemoglobin pada siswi kelas X di MAN 3 Magetan. Desain penelitian menggunakan kuasi eksperimen dengan pendekatan one group pre-test dan post-test. Sebanyak 122 siswi usia 15–18 tahun menjadi responden berdasarkan kriteria inklusi dan persetujuan orang tua. Intervensi berupa pemberian TTD dilakukan seminggu sekali selama tiga bulan. Kadar hemoglobin diukur sebelum dan sesudah intervensi menggunakan alat HemoCue, dan data dianalisis dengan uji Wilcoxon Signed-Rank. Hasil menunjukkan peningkatan signifikan kadar hemoglobin setelah intervensi (p < 0,05). Sebelum intervensi, 39% siswi mengalami anemia, sementara setelahnya hanya 8%, dengan 92% memiliki kadar hemoglobin normal. Temuan ini menunjukkan bahwa pemberian TTD secara rutin efektif meningkatkan kadar hemoglobin dan menurunkan prevalensi anemia. Program ini perlu dilanjutkan secara berkelanjutan dengan edukasi gizi dan pemantauan kepatuhan konsumsi untuk hasil jangka panjang.